2019
DOI: 10.1177/2325967119847470
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Judo-Related Injuries in 21 Seasons of Competitions in France: A Prospective Study of Relevant Traumatic Injuries

Abstract: Background: Judo is a full-contact fighting sport that may lead to severe injuries. There are limited data available on the incidence of judo-related injuries. The French Judo Federation has established a surveillance system to document the frequency and type of injuries during judo competitions. Purpose: To describe the incidence rates and types of judo-related traumatic injuries during 21 seasons of competitions in France with respect to athlete (judoka) age, sex, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 39 publications
1
43
1
12
Order By: Relevance
“…In this study, the most frequent types of injuries were sprains/ligament injuries, followed by fractures and dislocations. Our results were similar to those reported by Frey et al 6) , and many severe injuries, including fractures and dislocations, have been reported in Mongolia. In addition, injuries that had occurred >1 year ago account for half of the injuries in this study, and we believed that severe injuries may have been prolonged.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the most frequent types of injuries were sprains/ligament injuries, followed by fractures and dislocations. Our results were similar to those reported by Frey et al 6) , and many severe injuries, including fractures and dislocations, have been reported in Mongolia. In addition, injuries that had occurred >1 year ago account for half of the injuries in this study, and we believed that severe injuries may have been prolonged.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the type of judo-related injuries, Pocecco et al 5) further reported that the most frequent injury types were sprains (5.6-59.8%), strains (7-33.8%), and contusions (5.6-59.8%). Moreover, Frey et al 6) reported that the most frequent judo-related traumatic injury types during 21 seasons of competitions in France were sprains (54.3%), followed by fractures (15.6%) and dislocations (12.5%). In this study, the most frequent types of injuries were sprains/ligament injuries, followed by fractures and dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…Two more recent studies evaluated the rate of UCL injury among combat sport participants. Frey and colleagues surveyed injury rates over 21 seasons of judo competitions in France evaluating over 400,000 matches involving 316,203 judokas [14]. The incidence of UCL sprains during this time period was found to be 17% of all injuries with a higher proportion involving more advanced practitioners competing in national competitions as compared with more amateur athletes.…”
Section: Epidemiology Of Elbow Injuries In Non-throwing Sportsmentioning
confidence: 99%
“…The rate of injury ranges between 12.3% and 30% [ 16 , 17 ]. Data on a large population (all ages and levels of performance) of French judokas during contests showed an injury incidence slightly above 1.1% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%